All about capsular tension rings. Issue 1 (January 2015) - Weber, Charles H.; Cionni, Robert J.
<x xml:space="preserve">Abstract</x> Purpose of review To discuss capsular tension devices and recent evidence regarding their use. Recent findings The capsular tension ring, modified capsular tension ring, and capsular tension segment are well established tools for use during phacoemulsification when zonular instability is present. Recent research has provided additional evidence of their benefits in decreasing intraoperative and postoperative complications. Summary Endocapsular support devices allow for cataract surgery success in the setting of zonular instability.